PERBANDINGAN KUALITAS KEHIDUPAN SOSIAL MASYARAKAT YANG BEKERJA PADA SEKTOR FORMAL DAN YANG BEKERJA PADA SEKTORINFORMAL - Yulita Santi Pentury; Yusdam Arrang Bua' (JURNAL KRITIS (Kebijakan, Riset, dan Inovasi), 2017)
The aim of this research to find out whether there was a significant difference between the social life quality of community that work in the formal and informal sector in Mimika regency.To mesuare the quality of social life of community that work in the formal and informal sector in Mimika regency, used four indicators namely ethics, aesthetic, religious and social value.Data collecting done by literature study, observation and questionnaire. To analyze the data that obtained used frequency distribution analysis by giving scala to the question than compare the quality of social life of community that work in formal and informal sector in Mimika regency.Based on the results of the research, there was not the significant difference of quality partially and simultaneously between social life of community that work in the formal and informal sector in Mimika regency. Partial was done by comparing the value of X2 table and value of X2 count. The partial test results done by comparing between value of Dtable and Do. Value of Do obtained is 0.22 while the value of Dtable obtained from each indicators are the ethical value of 0.01, aesthitic value of 0.16, religious value of 0.04 and the social value of 0.03. From value of Dtable obtained in all indicators of the quality of social life of community is lower than the value of Do so that partially there was not significant difference in quality between social life of community that work in the formal and informal sector in Mimika regency. While simultaneous test is done by comparing the value of Do and Dtable obtained Do < Dtable is 0.03 <0.11 Ho is rejected and Hi is accepted rejected which means there was not significant quality difference simultaneously between the social life of community that work in the formal and informal sector in Mimika regency.